How Do Average Hours Worked Vary with Development? Cross-Country Evidence and Implications - Nicola Fuchs-Schündeln; Alexander Bick; David Lagakos (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
How do average hours worked vary across the world income distribution? To answer this question, we build a new internationally comparable database of hours worked covering countries of all income levels. We document that average hours worked per adult are substantially higher in low-income countries than in high-income countries. This pattern holds for both men and women, for adults of all ages and education levels, and along both the extensive margin (employment rates) and intensive margin (hours per worker). Our results imply that labor productivity and welfare differences across countries are larger than suggested by differences in consumption per capita.
Keywords: E01; E24; J22; 330